PERENCANAAN STRUKTUR BAJA PADA GEDUNG TOSERBA BALE ENDAH - Ramadhan, Yusran Fakih; -, Sutrisno (Jurnal Mahasiswa Terapan; Vol 1 No 4 (2025): Jurnal Mahasiswa Terapan, 2025)
With the growth of the urban population, department stores are a solution by providing various goods in one place, making it easier for urban consumers. Urbanization creates the need for comprehensive shopping centers. Before building a department store building, it is necessary to consider land conditions and earthquake-resistant foundation design. Building and structure designs, including foundations, beams, columns, slabs and soil bearing capacity, are planned according to SNI standards using the SAP 2000 v.22 application. The aim of planning this department store building is to achieve safe building dimensions. The structural planning carried out in this research uses manual methods or software such as SAP2000.